Study on Diagnostic Approach for Pleural Effusion with Varied Etiology: Study on Diagnostic Approach for Pleural Effusion with Varied Etiology - V, Shivpuje Anjali; G, Page Shrikant (National Journal of Integrated Research in Medicine, 2017)
Background: Pleural effusion is a commonest condition in clinical practice. Determining the cause of pleural effusion is not always easy. Proper history, clinical examination and investigations including pleural fluid studies may reveal etiological diagnosis of pleural effusion. Objective: In this study an attempt has been made to arrive at the etiological diagnosis by clinical profile of pleural effusion. Methods: A prospective study of 50 cases of pleural effusion was carried out in Department of Medicine, over period of two year. Cases admitted in Medicine and chest and TB ward were studied. The diagnosis of pleural effusion was done by detail history, physical examination and was then confirmed by chest x ray. Etiological diagnosis of pleural effusion was then confirmed by pleural fluid studies, like PH, pleural fluid protein, cytology. Results: Incidence of pleural effusion was more common in age group 20 – 50 years. Male predominance was more than females in both the groups. Tuberculosis was the commonest cause of exudative pleural effusion. Majority of tuberculous pleural effusion were right sided. Conclusion: Tuberculous pleural effusion is most common etiology followed by parapnemonic. Tuberculosis was the commonest cause of exudative pleural effusion. [Shrikant G NJIRM 2017; 8(4):63-67]